Changes in volatile composition during fruit development and ripening of `Alphonso' mango - Pandit, Sagar S.; Kulkarni, Ram S.; Chidley, Hemangi G.; Giri, Ashok P.; Pujari, Keshav H.; Koellner, Tobias G.; Degenhardt, Joerg; Gershenzon, Jonathan; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2009)
BACKGROUND: Volatile blends of five developing and five ripening stages of mango (Mangifera indica L. cv. Alphonso) were investigated along with those of flowers and leaves. Raw and ripe fruits of cv. Sabia were also used for comparison. RESULTS: A total of 55 volatiles belonging to various chemical classes such as aldehydes, alcohols, mono- and sesquiterpene hydrocarbons, lactones and furanones were identified. In all Alphonso tissues monoterpenes quantitatively dominated, with 57-99% contribution; in particular, (Z)-ocimene was found in the highest amount. Ripeness was characterized by the de novo appearance of lactones and furanones in the blend of monoterpenes. Sabja was distinguished by the abundance of monoterpene hydrocarbons in the raw fruit, and that of sesquiterpene hydrocarbons and their derivatives in the ripe stage. CONCLUSION: Various stages of the Alphonso fruit during transition from flower to ripe fruit are characterized by unique volatile signatures that are distinguished from each other by the qualitative and quantitative appearance of different volatile compounds. Thus volatiles can be highly informative markers while studying the development and ripening of mango. (C) 2009 Society of Chemical Industry
Keywords: Deogad; Gas chromatography; Mangifera indica; mango products; ripening indicator; Sabja

Cultivar relationships in mango based on fruit volatile profiles - Pandit, Sagar S.; Chidley, Hemangi G.; Kulkarni, Ram S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2009)
Aroma volatiles of mango (Mangifera indica L.) determine consumer acceptability and influence selection, whilst breeding. To assess their variety, composition and possible impact on cultivar relationships, volatile blends of 22 Indian and five non-Indian cultivars were investigated using solvent extraction and gas chromatography. Totally 84 volatiles belonging to various chemical classes were detected. Based on the Cumulative Occurrence of members of these classes, cultivars were grouped as monoterpene or sesquiterpene dominant. a-Pinene, beta-myrcene and beta-caryophyllene were found in all 27 cultivars. For ordination, common compounds with high (relative) concentration provided quantitative characters, whereas the rare and lesser ones provided qualitative (binary) characters; non-Indian cultivars separated from Indian ones but displayed close relations within their groups. In conclusion, mango flavour is dominated qualitatively as well as quantitatively by terpene hydrocarbons; ancient selection of mango cultivars is hinted to be driven by different aroma characters in different parts of the world. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Flavour; GC-MS; Mangifera indica; Multivariate analysis; Ordination

Characterization of three novel isoprenyl diphosphate synthases from the terpenoid rich mango fruit - Kulkarni, Ram; Pandit, Sagar; Chidley, Hemangi G.; Nagel, Raimund; Schmidt, Axel; Gershenzon, Jonathan; Pujari, Keshav; Giri, Ashok P.; Gupta, Vidya (Plant Physiology and Biochemistry, 2013)
Mango (cv. Alphonso) is popular due to its highly attractive, terpenoid-rich flavor. Although Alphonso is clonally propagated, its fruit-flavor composition varies when plants are grown in different geo-climatic zones. Isoprenyl diphosphate synthases catalyze important branch-point reactions in terpenoid biosynthesis, providing precursors for common terpenoids such as volatile terpenes, sterols and carotenoids. Two geranyl diphosphate synthases and a farnesyl diphosphate synthase were isolated from Alphonso fruits, cloned for recombinant expression and found to produce the respective products. Although, one of the geranyl diphosphate synthases showed high sequence similarity to the geranylgeranyl diphosphate synthases, it did not exhibit geranylgeranyl diphosphate synthesizing activity. When modeled, this geranyl diphosphate synthase and farnesyl diphosphate synthase structures were found to be homologous with the reference structures, having all the catalytic side chains appropriately oriented. The optimum temperature for both the geranyl diphosphate synthases was 40 degrees C and that for farnesyl diphosphate synthase was 25 degrees C. This finding correlated well with the dominance of monoterpenes in comparison to sesquiterpenes in the fruits of Alphonso mango in which the mesocarp temperature is higher during ripening than development. The absence of activity of these enzymes with the divalent metal ion other than Mg2+ indicated their adaptation to the Mg2+ rich mesocarp. The typical expression pattern of these genes through the ripening stages of fruits from different cultivation localities depicting the highest transcript levels of these genes in the stage preceding the maximum terpene accumulation indicated the involvement of these genes in the biosynthesis of volatile terpenes. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Alphonso; Flavor variation; Fruit; Isoprenyl diphosphate synthase; Mangifera indica; Terpene volatiles